Strategi Kualitas Pelayanan Bongkar Muat Petikemas Empty Di Depo Armaco Semarang - Agus Pamungkas; Tini Utami; Victor Wiku (Dinamika Bahari, 2020)
The empty container depot business activity is basically a service for loading and unloading activities (loading and unloading) or export and import activities carried out by exporters and importers, especially in Central Java. The purpose of this study is to determine the management of activities carried out in an empty container depot in the operation of loading and unloading empty containers at the container depot. The research method used in this study is a qualitative method, by conducting field surveys, interviews with actors, discussions, and reviewing related literature. The strategy for the quality of empty container loading and unloading services is no less important than other operational services such as trucking, shipping, forwarding, and others. The skills and skills of human resources and equipment in maintaining and repairing container loading and unloading equipment must be continuously developed.